2018
DOI: 10.1038/s41598-018-19547-z
|View full text |Cite
|
Sign up to set email alerts
|

Young and healthy C57BL/6 J mice performing sprint interval training reveal gender- and site-specific changes to the cortical bone

Abstract: Physical exercise is considered to impede the bone loss associated with physiological ageing however, a training program that efficiently leads to bone accrual in the healthy does not yet exist. We turned to the C57BL/6 J mouse and designed a sprint interval training for treadmill that was tailored to the individual performance limits. It consisted of four weeks with five training sessions each, followed by another four weeks with three. After completion of the training period, mice were sacrificed and the hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Our μCT data further suggested that even though OVX decreased the trabecular bone mass, treadmill training had no additional impact, neither positive nor negative. These observations are in line with previous publications, showing a lack of exercise-associated changes at the proximal tibia and the vertebral bodies alike (Iwamoto et al, 1999;Bennell et al, 2002;Hollinski et al, 2008). This distinctive feature of the trabecular bone is difficult to explain and has in the past been interpreted as a consequence from females accumulating trabecular bone mass in excess of the optimal bone mass, in order to provide a buffer against the bone loss during lactation (Bennell et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our μCT data further suggested that even though OVX decreased the trabecular bone mass, treadmill training had no additional impact, neither positive nor negative. These observations are in line with previous publications, showing a lack of exercise-associated changes at the proximal tibia and the vertebral bodies alike (Iwamoto et al, 1999;Bennell et al, 2002;Hollinski et al, 2008). This distinctive feature of the trabecular bone is difficult to explain and has in the past been interpreted as a consequence from females accumulating trabecular bone mass in excess of the optimal bone mass, in order to provide a buffer against the bone loss during lactation (Bennell et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…We and others have evidence that longer training periods may be required before a true remodeling and bone accrual can be detected (Hollinski et al, 2008;Hsu et al, 2018). We have previously shown that while 4 weeks of high intensity interval training in young and healthy mice led to a reduction of the tibial cortical thickness, another 4 weeks of training reversed this finding (Hollinski et al, 2008). Likewise, Hsu et al (2018) showed the upregulation of osteogenesis-related genes in osteoblasts of OVX C57BL/6 mice after 8 weeks of training.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations